2021
DOI: 10.4103/jfmpc.jfmpc_1141_20
|View full text |Cite
|
Sign up to set email alerts
|

Medication take-back programs in Qatar

Abstract: Purpose: To identify parental perception of a take-back program for medications. Materials and Methods: A cross-sectional study using a questionnaire was conducted at Hamad Medical Corporation, the only tertiary pediatric hospital in the State of Qatar at the time of the study. Qatar is a rapidly developing country with limited national data on the awareness of medication misuse among adults living with children at home and on the safety practices regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…This finding was consistent with a finding from a previous study, in which the participants pharmacists’ response that there was no clear census policy on how to appropriately dispose of medication waste ( Lucca et al, 2019 , Alqurshi, 2020 ). The Food and Drug Authority (FDA), in United States, had launched several guidelines for the safe disposal of unused and expired medicine which includes the take-back program ( Hendaus et al, 2021 ). Such a program is not clearly defined and established in Saudi Arabia and no clear guidelines were established to govern the safe and proper disposal of medication waste ( Alhomoud, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with a finding from a previous study, in which the participants pharmacists’ response that there was no clear census policy on how to appropriately dispose of medication waste ( Lucca et al, 2019 , Alqurshi, 2020 ). The Food and Drug Authority (FDA), in United States, had launched several guidelines for the safe disposal of unused and expired medicine which includes the take-back program ( Hendaus et al, 2021 ). Such a program is not clearly defined and established in Saudi Arabia and no clear guidelines were established to govern the safe and proper disposal of medication waste ( Alhomoud, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar study indicated that 51.8 % (n = 199) of the respondents were unaware of medication waste, and 60.7 % (n = 233) did not hear about medications’ proper disposal instructions. Respondents not hearing about unwanted medications take-back programs was confirmed by another Qatar-based study; however, almost 60 % of these respondents stated that they would utilize such programs if available [ 21 ]. Conversely, a similar study indicated that inappropriate disposal occurred due to lack of awareness about how to treat expired medications [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous findings [ 32 , 36 ], almost half of the respondents in this study (47.8 %, n = 196) had unused medications in their homes at the time of completing the questionnaire. Another study in Qatar revealed that almost 60 % of parents declared that they keep unused medications at home [ 21 ]. In the present study, having unused medications in the patient's home was significantly associated with age group (χ 2 = 16.846, p = 0.032), nationality (χ 2 = 39.133, p < 0.001), household income (χ 2 = 25.262, p < 0.001), and occupation (χ 2 = 13.292, p = 0.039).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation